Public attitudes towards people living with dementia: A cross-sectional study in urban Japan (innovative practice). (February 2020) - Aihara, Yoko; Kato, Hisako; Sugiyama, Tetsuko; Ishi, Kuniko; Goto, Yasushi
Stigma and social isolation are major challenges in building dementia friendly communities. Information is a key factor in improving knowledge and attitudes about dementia. This cross-sectional survey aimed to investigate public attitudes towards people with dementia in an urban community in Japan. Nearly 90% of the participants responded that they were able to have a good relationship with a person with dementia and help such a person if needed. However, around half of the participants would be ashamed of a family member with dementia. A multiple regression model showed that information from television and educational classes was associated with positive attitudes towards people with dementia among older adults. Information from educational classes and the Internet was likewise associated with positive attitudes among the volunteers. Increasing the availability and accessibility of information on dementia may contribute to improving public attitudes towards people with dementia.